2005
DOI: 10.1111/j.1472-765x.2005.01657.x
|View full text |Cite
|
Sign up to set email alerts
|

Acetophenones with selective antimycobacterial activity

Abstract: Aims: Mycobacteria are a serious cause of infections in humans, with limited treatment options, as no new antibiotics have been developed against mycobacteria since the 1960s. In this study, the antimycobacterial activity of a small library of acetophenone (AP) compounds was analysed. Methods and Results: Twenty-three AP derivatives were examined for activity against mycobacteria using a microbroth assay. The compounds were bacteriostatic, with the most effective (cyclohexylacetophenone and piperidinoacetophen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 28 publications
2
23
0
Order By: Relevance
“…The obtained results were consistant with the findings of previous studies and suggested that due to the several possible reasons mentioned in our previous study, the most susceptible strains were Grampositive microorganisms (28). The antibacterial effects of acetophenone derivatives have been previously shown against Staphylococcus aureus (29,30). Therefore, the existence of 4, 6-di-methoxy acetophenone-2-O-β-D-glucopyranoside in 20% fraction and its antibacterial activity might be considered as a possible explanation for the inhibitory effect of the mentioned SPE fractions.…”
Section: Discussionsupporting
confidence: 91%
“…The obtained results were consistant with the findings of previous studies and suggested that due to the several possible reasons mentioned in our previous study, the most susceptible strains were Grampositive microorganisms (28). The antibacterial effects of acetophenone derivatives have been previously shown against Staphylococcus aureus (29,30). Therefore, the existence of 4, 6-di-methoxy acetophenone-2-O-β-D-glucopyranoside in 20% fraction and its antibacterial activity might be considered as a possible explanation for the inhibitory effect of the mentioned SPE fractions.…”
Section: Discussionsupporting
confidence: 91%
“…a,a 0 -(EE)-Bis(benzylidene)-cycloalkanones (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) were prepared by reacting 2 equivalents of aromatic aldehydes with 1 equivalent of cycloalkanones in the presence of solid KOH (5 mol%) in ethanol (Scheme 1). The selected aldehydes comprise furfuraldehyde, benzaldehyde, 4-bromobenzaldehyde, 4-chlorobenzaldehyde, 4-fluorobenzaldehyde, 4-nitrobenzaldehyde, 4-methoxybenzaldehyde, 3,4-dimethoxybenzaldehyde and 3,4,5-trimethoxybenzaldehyde.…”
Section: Chemistrymentioning
confidence: 99%
“…Recently, we have designed and developed novel aryloxy cyclopropyl phenyl methanones [10] as possible inhibitors of FAS-II enzyme which is required in chain elongation of mycolic acids keeping in mind the structure of triclosan [11] and the compounds displayed potent antitubercular activity both in vitro and in vivo. Moreover, several acetophenones [12], chalcones [13] and Mannich bases of benzylidene cycloalkanones [14] have also been disclosed to possess moderate antitubercular activity and their mode of action is also postulated to be the inhibition of initial steps in fatty acid biosynthesis. Bis-benzylidene cycloalkanones have been reported to possess drug resistance reversal [15], cytotoxicity [16] and histone acetyl transferase (HAT) [17] inhibitory activities.…”
Section: Introductionmentioning
confidence: 98%
“…. A recent screen of acetophenone derivatives revealed that some of these compounds have significant anti-mycobacterial properties [50]. Acetophenonederivaties with the strongest antibiotic properties were subsequently tested in the HeLa-GFP cytotoxicity assay to determine if any of these compounds exhibited cytotoxic effects against the human cell line (see Fig.…”
Section: Recent Gfp-assays For Drug Discoverymentioning
confidence: 99%
“…Acetophenonederivaties with the strongest antibiotic properties were subsequently tested in the HeLa-GFP cytotoxicity assay to determine if any of these compounds exhibited cytotoxic effects against the human cell line (see Fig. 3; [50]). This analysis uncovered compounds with selective cytotoxicity toward eukaryotic cells (see asterisks, Fig.…”
Section: Recent Gfp-assays For Drug Discoverymentioning
confidence: 99%